Quantifying the effect of solution formulation on the removal of soft solid food deposits from stainless steel substrates. (February 2019) - Cuckston, G.L.; Alam, Z.; Goodwin, J.; Ward, G.; Wilson, D.I.
Abstract: The role of detergent formulation on the cleaning of a complex carbohydrate-fat food soil from stainless steel surfaces was studied using a modified version of the millimanipulation device described by Ali et al. (2015b) which allowed the force required to scrape the soil from the surface to be measured as the soil is immersed, in situ and in real time. This allowed the influence of temperature, solution chemistry and time on the mechanical forces (rheology) and removal behaviour of the soil to be studied – in effect quantifying the relationships in Sinner's cleaning circle. The soil simulated a burnt-on baked-on deposit and featured regular cracking in the 300 μm thick layer. The removal force decreased noticeably on hydration: the cleaning mechanism was then determined by the agents present. At 20 °C, below the temperature at which the fat phase was mobile, removal was characterised by cohesive failure except in the presence of the cationic surfactant CTAB, which promoted adhesive failure and fast decay in removal force. At 50 °C, when the fat was mobile, a transition between cohesive and adhesive failure was observed at pH 7 which was inhibited at higher pH. Adhesive failure and fast decay in removal force was observed at higher pH and 50 °C in the presence of the anionic and non-ionic surfactants, SDBS and TX-100, respectively. Graphical abstract: Image 1 Highlights: Force required to peel off an immersed soil layer measured in real time. Adhesion of burnt protein/fat/starch soil decreases upon hydration. A transition from cohesive to adhesive removal is identified. The effect of surfactant type on removal mechanism is monitored quantitatively. Surfactants were more effective at reducing adhesion forces at higher temperature.